Colonial, economic rationalist, or collegial? Indonesian business leaders' perceptions (2001) of G7 behaviour - Daale, Peter (Curtin University, 2003)
This research project aims to determine Indonesian business leaders perceptions of G7 behaviour towards Indonesia after Independence (1945/1949), at a time when the country is experiencing a severe financial and economic crisis (1997-2001). Is G7 behaviour considered colonial, economic rationalist, or collegial? Additionally, Indonesian business leaders' perceptions of economic and social development in Indonesia are measured, exploring a possible connection with perception of G7 behaviour. Within the context of this project, the researcher assumes that attitudes in Indonesia are significantly shaped by the impact of' an increasingly competitive and sophisticated global free-trade environment today versus one of exploitation and domination under past European colonial rule. The research questions on which the project is based emerged after detailed consideration of a large and varied number of publications concerning related historical and contemporary socio-economic, political issues and examination of recent inter-country comparative performance indicators (1996 to 2000). The background for the research project is framed within the context of Modern World-Systems theory which rose to prominence in the early 1970s, earlier theories about Intentional Underdevelopment, Dependency and Geography, and the more recent hypothesis on Enlightenment and Institutions theory, all attempting to explain why some countries are so poor and others are not. An exploratory study (Study 1) precedes the positivist research paradigm of the principal study (Study 2 - Stages 1 & 2), which is comprised of a pilot and a final stage.The theoretical model put forward and corresponding final stage VIII cross-sectional survey data of the second study are subjected to structural equation modeling (SEM) analysis, to test hypotheses and theory about the associations between theoretical constructs of the model. SEM is a relatively new multivariate technique, which combines aspects of multiple regression and factor analysis. The results of the research show that the impact of colonial rule; the associated exploitation and consequent poverty are still remembered by Indonesian business leaders and as such may have the potential to negatively impact on bi-lateral and multi-lateral negotiations for much needed structural reform in Indonesia, particularly if key influential participants (such as the G7 and the international institutions they control) ignore historical legacies and associated cross-cultural sensitivities. Final stage results provided strong support for two out of the five key hypotheses offered. The findings clearly suggesting that intensifying G7 behaviour as defined in this thesis would invariably further heighten existing perceptions of colonial behaviour. Less encouraging test results were obtained for the remaining hypotheses and overall only qualified support could be given to the proposed theory.The extent of which can be summarized as: "G7 behaviour is perceived as colonial, by Indonesian business leaders, and is significantly influenced by their perception of social development in Indonesia ". The research project was conceived in the absence of scholarly investigations into the historical impact of colonialism in Indonesia on present day attitudes and cultural values with respect to ready acceptance of predominantly Western concepts of globalisation, free trade, open markets and the need for crucial reform. Reforms, which often are imposed on developing nations during times of crisis by way of IMF - Structural Adjustment Programmes (SAP), harshly impacting on local populations.